Change in expressed emotion and treatment outcome in adolescent anorexia nervosa. Issue 1 (1st January 2017) - Moskovich, Ashley A.; Timko, C. Alix; Honeycutt, Lisa K.; Zucker, Nancy L.; Merwin, Rhonda M.
ABSTRACT: Expressed emotion (EE) has been associated with poor outcomes in anorexia nervosa (AN); however, whether changes in EE predict superior treatment outcomes is unknown. The current study examined whether decreases in EE during an open trial of a novel family-based treatment for AN predicted symptoms at end of treatment. Forty-seven adolescents (12–18 years of age) with AN or sub-threshold AN and their parents (mothers: n = 47, fathers: n = 39) participated in 6 months of family treatment. Measures of AN symptomatology (Eating Disorder Examination completed by adolescent and end of treatment recovery status) and parental EE (Family Questionnaire completed by parents which measures two facets of EE: critical communication [CC] and emotional over-involvement [EOI]) were collected at baseline and end of treatment. Parental EOI, but not CC, significantly decreased during the course of treatment. Change in mothers', but not fathers', EE accounted for additional variance in AN symptomatology at end of treatment above baseline EE and baseline AN symptom levels. Findings suggest a greater emphasis on parent support during treatment may improve outcomes.